SUISTANABLE DEVELOPMENT GOALS (SDGS) TROUGH AGRICULTURAL FINANCING IN ISLAMIC BANKING - Sihotang, Mutiah Khaira (Proceeding International Seminar of Islamic Studies, 2023)
Indonesia is a country with an agrarian background, which means that the agricultural sector plays an important role in the Indonesian economy. One of the main problems in development in the agricultural sector is weak capital. The agricultural sector is a real sector capable of supporting the realization of the Sustainable Development Goals (SDGs). This research is descriptive qualitative which describes financing in the agricultural sector that is able to support the realization of the Sustainable Development Goals (SDGs), especially in the economic field. The results of this study explain that the Islamic economic SDGs can be achieved through agricultural development. This is because the agricultural sector has an important role in improving the economy which will automatically alleviate poverty. So it can be concluded that one way to achieve the SDGs is through the agricultural sector. The agricultural sector has a fundamental role in meeting basic human needs.